PENYIMPANGAN STRUKTUR FRASA BAHASA INDONESIA PADA SPANDUK DAN PAPAN NAMA DI KABUPATEN BANTUL (INDONESIAN IRREGULARITIES PHRASE STRUCTURE AT THE BANNERS AND SIGNAGE IN THE DISTRICT BANTUL) - Aji Prasetyo (Kadera Bahasa, 2016)
Language plays an important role in the communication process. Language used in outdoor media, such as hotel signage, store signage, and banners. The author still find much errors, particularly the structure of the writing of a group of words or phrases in the banner and the signage. The theory used in this study is diterangkan-menerangkan legal norms (D-M), while the methodological approach used is descriptive qualitative approach. Data collection is performed using the method of direct observation (observation), technical notes, and documentation. Data analysis was performed having regard to the various aspects and types of errors. The results of the data analysis presented informalpresentation method that is the presentation without the use of a particular sign or symbol. The results obtained, namely (1) the error occurred in the consumer’s attention or community efforts, (2) the error occurred because the structure of phrases used are considered more prestigious, and (3) the error occurred because of the use of the word uptake is more prevalent in society.